Faecal calprotectin for differentiating between irritable bowel syndrome and inflammatory bowel disease: a useful screen in daily gastroenterology practice. Issue 1 (2nd April 2014) - Banerjee, Ashwini; Srinivas, M; Eyre, Richard; Ellis, Robert; Waugh, Norman; Bardhan, K D; Basumani, P
Abstract : Objective: To determine the best faecal calprotectin (FCP) cut-off level for differentiating between irritable bowel syndrome (IBS) and organic disease, particularly inflammatory bowel disease (IBD), in patients presenting with chronic diarrhoea. Design: Retrospective analysis of patients who had colonoscopy, histology and FCP completed within 2 months. Setting: District general hospital. Patients: Consecutive new patients with chronic diarrhoea lasting longer than 4 weeks. Interventions: Patients were seen by a single experienced gastroenterologist and listed for colonoscopy with histology. Laboratory investigations included a single faecal specimen for calprotectin assay (lower limit of detection: 8 µg/g), the results used for information only. Main outcome measures: Six FCP cut-off levels (range 8–150 µg/g) were compared against the 'gold standard' of histology: inflammation 'present' or 'absent'. Results: Of 119 patients studied, 98 had normal colonoscopy and histology. The sensitivity of FCP to detect IBD at cut-off levels 8, 25 and 50 µg/g was 100% (with corresponding specificity 51%, 51%, 60%). In contrast, the lowest FCP cut-off, 8 µg/g, had 100% sensitivity to detect colonic inflammation, irrespective of cause (with negative predictive value (NPV) 100%). Importantly, 50/119 patients (42%) with FCP <8 µg/g had normal colonoscopy and histology. Conclusions: Our results suggest that using FCP to screen patients newly referred for chronic diarrhoea could exclude all without IBD and, at a lower cut-off, all without colonic inflammation, thus avoiding the need for colonoscopy. Such a major reduction has implications for resource allocation.